2007
DOI: 10.1539/joh.49.509
|View full text |Cite
|
Sign up to set email alerts
|

Biological Monitoring of Pyrethroid Exposure of Pest Control Workers in Japan

Abstract: Biological Monitoring of Pyrethroid Exposure of Pest Control Workers in Japan: Dong WANG, et al. Department of Radiological and MedicalLaboratory Sciences, Nagoya University Graduate School of Medicine-Synthetic pyrethroids such as cypermethrin, deltamethrin and permethrin, which are usually used in pest control operations, are metabolized to 3-phenoxybenzoic acid (3-PBA) and excreted in urine. Though 3-PBA can be used to assess exposure to pyrethroids, there are few reports describing urinary 3-PBA levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 24 publications
1
25
1
1
Order By: Relevance
“…In our previous study, the GM of 3-PBA levels in urine collected from Japanese pest control operators in summer was 12.2 μg/g creatinine (Wang et al, 2007), > 30-fold higher than GMs obtained in the present study. These results clearly indicated dramatically high levels of exposure among pest control operators in comparison with the non-spraying population.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In our previous study, the GM of 3-PBA levels in urine collected from Japanese pest control operators in summer was 12.2 μg/g creatinine (Wang et al, 2007), > 30-fold higher than GMs obtained in the present study. These results clearly indicated dramatically high levels of exposure among pest control operators in comparison with the non-spraying population.…”
Section: Discussioncontrasting
confidence: 74%
“…In our previous study, 3-PBA has been quantified in the urine of pest control operators (PCOs) exposed to PYR during handling, mixing, and spraying (Wang et al, 2007). In the absence of data on the urinary 3-PBA levels derived from non-occupational PYR exposure, however, we considered that risks resulting from PYR exposures among PCOs might not be adequately assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The urinary 3-PBA levels among Japanese pest control operators (PCOs) have been previously reported by our colleagues [33], who found that the geometric means of 3-PBA c concentrations in their study population of PCOs, who had been occupationally exposed to PYRs, were 12.2 lg/g creatinine in the summer and 3.9 lg/g creatinine in the winter. These levels clearly indicate that such workers were exposed to higher doses of PYRs than the individuals of our study population.…”
Section: Discussionmentioning
confidence: 57%
“…These values are of course generally lower than those detected in populations with occupational exposure; geometric means of urinary 3-PBA of pest control operators (PCOs) who sprayed PYRs within 2 days before urine collection were 12.3 mg/g creatinine (range, ϽLOD-226) for summer season and 5.5 mg/g creatinine (range, ϽLOD-76) for winter. 47) Hardt and Angerer 48) have reported that the median levels of urinary 3-PBA in agriculture workers (nϭ19, 24 urine samples), PCOs (nϭ15, 29 urine samples) and greenhouse workers (nϭ2, 7 urine samples) were 0.6 mg/l (range, ϽLOD-28.5), 1.4 mg/l (range, ϽLOD-57.5) and 2.9 mg/l (range, ϽLOD-26.0), respectively. It should be emphasized that reference values are merely statistically derived without consideration of the health status and thus cannot be used to discuss causal relationships between exposure and health outcomes of the individuals.…”
Section: Results Unitsmentioning
confidence: 99%